The Impact of Work Discipline and Leadership on Teacher Performance - Naimar Naimar; Herispon Herispon; Faira Medina Dzikra (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2024)
Purpose–This study attempts to examine how the work discipline of teachers and the leadership of the principal affect the performance of teachers at the Al Huda Pekanbaru school. Methodology–Data was collected by teachers at Al Huda Pekanbaru school completing out questionnaires. 52 teachers at the Al Huda Pekanbaru school made up the study's population; each was a sample (saturated sample). Findings– Principal leadership and teacher performance were found to have a strong positive relationship and influence. Workplace discipline among teachers has a strong positive correlation with their effectiveness. The principal's leadership and the teachers' work discipline have a substantial positive relationship and impact on the teachers' performance. Novelty-there will be a positive tendency for teacher performance if the principal's leadership and the discipline of the teachers' work are both enhanced.